Phytoplankton physiology in a nearshore region of the southern Benguela current - Barlow, Raymond Gordon (Department of Biological Sciences, 2016)
During the summer of 1978-79 diatoms dominated the communities from October to January but microflagellates were dominant in February and March. Low concentrations of ATP, chlorophyll a protein and carbohydrate were measured in Type 1 water with protein/carbohydrate ratios being )1. In Type 2 water concentrations of chlorophyll a ATP and protein were high and the protein/carbohydrate ratio was)l. Concentrations of chlorophyll a and ATP remained high in Type 3 water but the protein/carbohydrate ratio decreased to <1 due to an increase in the concentration of acid-soluble glucan. It was concluded that the communities were in an active phase of growth in Type 1 and Type 2 water when adequate nutrients were available, but were in a slow-growing phase in Type 3 water when nitrate concentrations were low.